2017
DOI: 10.1002/jcp.25829
|View full text |Cite
|
Sign up to set email alerts
|

High glucose alters the secretome of mechanically stimulated osteocyte‐like cells affecting osteoclast precursor recruitment and differentiation

Abstract: Diabetes mellitus (DM) induces bone deterioration, while mechanical stimulation promotes osteocyte-driven bone formation. We aimed to evaluate the interaction of acute exposure (24 h) to high glucose (HG) with both the pro-survival effect conferred to osteocytic MLO-Y4 cells and osteoblastic MC3T3-E1 cells by mechanical stimulation and the interaction of these cells with osteoclast precursor RAW264.7 cells. We found that 24 h of HG (25 mM) pre-exposure prevented both cell survival and ERK and β-catenin nuclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…To analyze C3‐mediated toxicity in osteoclasts, hydrogel alone or hydrogel loaded with C3‐derived recombinant fusion toxin C2IN‐C3lim‐G205C were incubated with RAW 264.7 cells in osteoclastogenic medium. The RAW 264.7 cell is a well‐characterized preosteoclastic cell line, which is widely used as a model for osteoclast formation and activity . Preliminary experiments showed that these cells were, like J774A.1 cells, susceptible to the cytotoxic effect of the recombinant fusion toxin (Figures S1 and S2, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…To analyze C3‐mediated toxicity in osteoclasts, hydrogel alone or hydrogel loaded with C3‐derived recombinant fusion toxin C2IN‐C3lim‐G205C were incubated with RAW 264.7 cells in osteoclastogenic medium. The RAW 264.7 cell is a well‐characterized preosteoclastic cell line, which is widely used as a model for osteoclast formation and activity . Preliminary experiments showed that these cells were, like J774A.1 cells, susceptible to the cytotoxic effect of the recombinant fusion toxin (Figures S1 and S2, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…You et al () have found that fluid shear stress stimulation for 2 hr had no changes in sRANKL of MLO‐Y4 cells, but decreased osteoclast formation. The results from Maycas et al () showed that high glucose induced no significant change of RANKL expression from MLO‐Y4 cells, but induced decease of osteoclast activity. Thus, the findings from both our current study and other groups indicated that RANKL may not be the only molecule that secreted by osteocytes to control osteoclast formation and activity, and some other molecules (e.g., M‐CSF and VEGF) may also contribute to the regulation of osteoclast functions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of our group have shown that HG affects osteocyte mechanotransduction, especially osteocyte-osteoclast communication, suggesting new pathways to link the mechanisms involved in the deleterious effects of DM in the skeleton 14 . We emphasized that the analysis of the metabolic secretome may be critical to obtain new insights into this process and the role of HG levels in these effects.…”
Section: Discussionmentioning
confidence: 89%
“…No significant changes in cell viability were observed between the different experimental conditions (with or without HG and/or FF). The details of the experiment can be found in a previously published article 14 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation